Natural Semantic Metalanguage as an approach to measuring meaning - Cavanagh, Robert Frederick; Asano-Cavanagh, Yuko; Fisher (Jr), William P (Institute of Physics (IoP), 2019)
Do any interesting or valuable fundamental commonalities arise when measurement and linguistic methods are used to understand the same phenomena? A basis for such commonality resides in the human desire for meaning, a need manifest in all cultures and languages. However, the notion of meaning is rarely associated with measurement; it resides more comfortably in the study of language and linguistics. This exploration commences with an examination of measurement theories, principally Rasch Measurement Theory (RMT), with the aim of identifying opportunities for elucidating the meaning of objects of measurement. A brief overview of the discipline of linguistics then reveals the importance of semantics in expressing meaning. An explanation of how the Natural Semantic Metalanguage (NSM) can enable explication of linguistic meaning follows. The paper concludes with a proposal for ecological applications of invariant measurement and the NSM.